Thermal Systems - Agnew, Brian; Tam, Ivan CK (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
We live in interesting times in which life as we know it is being threatened by manmade changes to the atmosphere in which we live. On the global scale, concern is focused on climate change due to greenhouse gas emissions, and on a national scale, atmospheric pollution produced by combustion processes is of concern. A possible approach is through the development of new ideas and innovative processes to the current practices. Among the available options, multi-generation processes such as the trigeneration cycle, battery storage system, solar power plants and heat pumps have been widely studied, as they potentially allow for greater efficiency, lower costs, and reduced emissions. On the other hand, some researchers had been working to increase the potential of energy generation process through heat recovery under the steam generator, organic Rankine cycle, and absorption chillers. In this Special Issue on "Thermal Systems" of fundamental or applied and numerical or experimental investigation, many new concepts in thermal systems and energy utilization were explored and published as original research papers in this "Special Issue".